Asuhan Keperawatan pada Bayi Ny. G & Ny. F yang Mengalami Resiko Kekurangan Nutrisi dengan Bayi Baru Lahir Normal di RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Manshur, Ihya Tadjmali; Umar, Ahmad Farid; Prihatini, Fitria (Jurnal Persada Husada Indonesia, 2024)
A normal newborn is a baby born in the back of the head through the vagina without using tools, at a gestational age of 37 weeks to 42 weeks, with a body weight of 2500-4000 grams, an Apgar score of >7, and no congenital defects. This research design uses qualitative research, namely research that attempts to describe a symptom, event, or incident that is happening now. Descriptive qualitative research with intervention is research that aims to explain the problem that will be addressed and what will be observed in the research. Descriptive research is research that presents a complete picture of the social setting and relationships contained in the research. Treatment of the risk of nutritional deficiencies must be carried out properly so that the risk of nutritional deficiencies can be avoided. Mothers of newborns and their families must also be educated about the risks of nutritional deficiencies, especially for mothers of newborns who are in their first pregnancy, and families who have no experience. Appropriate and correct actions and caring for newborns at risk of nutritional deficiencies. Priority nursing diagnoses for Mrs. G and baby Mrs. F, namely ineffective breastfeeding related to inadequate breast milk supply. The conclusion is that after carrying out nursing actions for 3 x 24 hours, observing the milk supply, and providing nursing techniques in nursing diagnoses for client 1 and client 2 has been resolved. Suggestion: to improve skills in providing nursing care for normal newborn babies.